2017
DOI: 10.1016/j.jprot.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of Pachyonychia congenita plantar callus

Abstract: Callus samples from the ball and the arch of the foot, collected on tape circles, were compared by shotgun proteomic profiling. Pachyonychia congenita subjects were sampled who exhibited a mutation in KRT6A, KRT6B, KRT6C, KRT16 or KRT17, and the proteins were digested and analyzed by tandem mass spectrometry. In comparison with samples from unaffected control subjects, those from subjects with KRT6A or KRT16 mutations displayed the most differences in profile from normal, while those from subjects with KRT6C o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Samples of epidermal squames were collected with CuDerm D110 D‐Squame Pro 2.2 cm adhesive circles from the forearms of 3 male and 3 female healthy individuals with informed consent (University of California Davis IRB#217868‐14) and eluted from the tapes as previously described . Some samples were processed with reduction and alkylation for mass spectrometry without fractionation, while others were separated into SDS‐dithioerythritol insoluble (envelope) and solubilized fractions .…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of epidermal squames were collected with CuDerm D110 D‐Squame Pro 2.2 cm adhesive circles from the forearms of 3 male and 3 female healthy individuals with informed consent (University of California Davis IRB#217868‐14) and eluted from the tapes as previously described . Some samples were processed with reduction and alkylation for mass spectrometry without fractionation, while others were separated into SDS‐dithioerythritol insoluble (envelope) and solubilized fractions .…”
Section: Experimental Designmentioning
confidence: 99%
“…Peptides were subjected to LC‐MS/MS analysis on a Thermo Scientific Q Exactive Plus Orbitrap mass spectrometer essentially as previously described . Intensity‐based absolute quantitation (iBAQ) values of samples analysed were used to calculate the relative molar amount of each protein .…”
Section: Experimental Designmentioning
confidence: 99%
“…Loricrin knockout (LKO) mice have impaired crosslinking of CE proteins (Rice et al, 2017), and total epidermal sheets were solubilized with a buffer containing sodium dodecyl sulfate and beta-mercaptoethanol to probe the FLG-repeat sequence (Yuspa et al, 1989) in the soluble protein fraction. As we previously described (Koch et al, 2000), LKO mice showed weaker signals in the monomeric 28-kDa FLG bands but stronger signals in the multimeric FLG bands (Figure 1a).…”
Section: To the Editormentioning
confidence: 99%
“…As we previously described (Koch et al, 2000), LKO mice showed weaker signals in the monomeric 28-kDa FLG bands but stronger signals in the multimeric FLG bands (Figure 1a). On the other hand, reflecting reduced gglutamyl lysine isopeptide crosslinks in the absence of LOR (Rice et al, 2017), SC from LKO mice showed smaller insoluble pellets compared with those from wild-type mice (Figure 1b). LKO mice showed higher amounts of both the monomeric and multimeric FLG bands compared with those from wildtype mice, as well as in the lowmolecular-weight bands that correspond to FLG breakdown peptides ( Figure 1c).…”
Section: To the Editormentioning
confidence: 99%
“…[37, 38] Comparisons with samples from unaffected control subjects revealed the protein profiles were most altered in samples from individuals with KRT6 or KRT16 mutations, while those from KRT6C or KRT17 mutations displayed few protein alterations. [39] The degree of departure from normal generally fit the observed severity of the syndrome for the keratin gene categories. Although not clearly contributing to understanding the mechanism of pain generation, a debilitating symptom, the results do provide a quantitative basis for noninvasive monitoring of treatment effectiveness.…”
Section: Epidermismentioning
confidence: 80%